MENYEIMBANGKAN KEAMANAN NEGARA DAN HAK ASASI MANUSIA: STUDI PERBANDINGAN INDONESIA DAN GAMBIA - Mendy, Kanchul Louis; Maskun (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2025)
This research examines the complex relationship between state security and human rights in Indonesia and The Gambia, two nations with distinct sociopolitical landscapes. In times of political unrest, terrorism, or civil conflict, efforts to ensure state security often compromise individual rights. The study explores how each country balances these competing demands, particularly during separatist movements, post-authoritarian transitions, and security crises. Using a comparative approach, it analyzes legal frameworks, institutional responses, and international commitments to human rights. The paper draws on recent case studies, including the Papua conflict in Indonesia and human rights reforms in The Gambia, to highlight ongoing challenges and strategies. The findings shed light on the broader global tension between surveillance-driven security measures and the protection of civil liberties.